Sung Tales from the Papua New Guinea Highlands Studies in Form, Meaning, and Sociocultural Context - Rumsey, Alan (ANU Press, 2011)
The genres of sung tales that are the subject of this volume are one of the most striking aspects of the cultural scene in the Papua New Guinea Highlands. Composed and performed by specialist bards, they are a highly valued art form. From a comparative viewpoint they are remarkable both for their scale and complexity, and for the range of variation that is found among regional genres and individual styles. Though their existence has previously been noted by researchers working in the Highlands, and some recordings made of them, most of these genres have not been studied in detail until quite recently, mainly because of the challenging range of disciplinary expertise that is required-in anthropology, linguistics, and ethnomusicology. This volume presents a set of interrelated studies by researchers in all of those fields, and by a Papua New Guinea Highlander who has assisted with the research based on his lifelong familiarity with one of the regional genres. The studies presented here (all of them previously unpublished and written especially for this volume) are of groundbreaking significance not only for specialists in Melanesia or the Pacific, but also for readers with a more general interest in comparative poetics, mythology, musicology, or verbal art.